2017
DOI: 10.1002/ajmg.a.38317
|View full text |Cite
|
Sign up to set email alerts
|

SERPINI1 pathogenic variants: An emerging cause of childhood‐onset progressive myoclonic epilepsy

Abstract: Progressive myoclonic epilepsies are rare neurodegenerative diseases with a wide spectrum of clinical presentations and genetic heterogeneity that render their diagnosis perplexing. Discovering new imputable genes has been an ongoing process in recent years. We present two pediatric cases of progressive myoclonic epilepsy with SERPINI1 pathogenic variants that lead to a severe presentation; we highlight the importance of including this gene, previously known as causing an adult-onset dementia-epilepsy syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…Additionally, EEGs revealed no photoparoxysmal response on intermittent photic stimulation also at low (1−3 Hz) frequencies. Behavioral abnormalities and failure at school were the first signs before seizure onset in our case, as in the case reported by Ranza et al [3] Therefore, neuroserpinosis should be included in the differential diagnosis of children with behavioral abnormalities and learning disabilities preceding PME in the first decade.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Additionally, EEGs revealed no photoparoxysmal response on intermittent photic stimulation also at low (1−3 Hz) frequencies. Behavioral abnormalities and failure at school were the first signs before seizure onset in our case, as in the case reported by Ranza et al [3] Therefore, neuroserpinosis should be included in the differential diagnosis of children with behavioral abnormalities and learning disabilities preceding PME in the first decade.…”
Section: Discussionsupporting
confidence: 81%
“…The parents did not carry this variation. Coutelier et al [2] and Ranza et al [3] reported the same aminoacid change (G392R) in the SERPINI1 gene in an 11-year-old girl with medication-refractory electrical status epilepticus of slow-wave sleep, and in a 12-year-old male with early-onset PME with assistance in all activities of daily living, respectively. Although the variation in the protein level is same as the previous two cases, the G to C transversion in nucleotide level has not been reported as a disease causing mutation to date.…”
Section: Casementioning
confidence: 87%
“…Of these serpins, which are involved in many regulatory processes, SerpinI1 (neuroserpin) is primarily secreted by axons in the brain, and may play a role in axonal growth and synaptic plasticity [66]. In humans, mutation in SERPINI1 lead to childhood-onset progressive myoclonic epilepsy [67] or familial dementia [68]. Amongst genes downregulated by exposure to VPA in our study was Ap2b1, which encodes an essential component of vesicle function, including synaptic vesicles [69].…”
Section: Discussionmentioning
confidence: 71%
“…Of these serpins, which are involved in many regulatory processes, SerpinI1 (neuroserpin) is primarily secreted by axons in the brain and may play a role in axonal growth and synaptic plasticity (68). In humans, mutation in SERPINI1 leads to childhood-onset progressive myoclonic epilepsy (61) or familial dementia (18). Among genes downregulated by exposure to VPA in our study was Ap2b1, which encodes an essential component of vesicle function, including synaptic vesicles (43).…”
Section: Discussionmentioning
confidence: 71%